2004
DOI: 10.1038/sj.ijo.0802730
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the stigma of obesity on overweight individuals

Abstract: OBJECTIVE:To investigate the internalization of anti-fat bias among overweight individuals across a variety of attitudes and stereotypes. DESIGN: Two studies were conducted using the Implicit Association Test (IAT), a performance-based measure of bias, to examine beliefs among overweight individuals about 'fat people' vs 'thin people'. Study two also contained explicit measures of attitudes about obese people. SUBJECTS: Study 1 participants were 68 overweight patients at a treatment research clinic (60 women, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
225
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(264 citation statements)
references
References 23 publications
24
225
4
5
Order By: Relevance
“…Moreover, unlike other stigmatized groups, obese women appear to internalize the negative perceptions toward obesity held by society and to devaluate themselves. 55 It may be that, at least for some obese women, increasing cumulative stress burden and poor self-concept eventually lower the threshold at which stress exposure may precipitate depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unlike other stigmatized groups, obese women appear to internalize the negative perceptions toward obesity held by society and to devaluate themselves. 55 It may be that, at least for some obese women, increasing cumulative stress burden and poor self-concept eventually lower the threshold at which stress exposure may precipitate depression.…”
Section: Discussionmentioning
confidence: 99%
“…Carels, Wott, Young, Gumble, Koball and Oehlhof (2010) found that being Caucasian was associated with greater implicit weight bias, while Powell and Kahn (1995) highlighted that racial differences in implicit weight bias may reflect the commonly observed racial differences in desires to be thin, particularly among Caucasian women. Similarly, Wang, Brownell and Wadden (2004) found that African Americans held less strong implicit weight bias compared to Caucasians. While Wang et al (2004) had originally hypothesised that African-American participants were less likely to show in-group devaluation than Caucasians, based on research by Ofosu, Lafreniere and Senn (1998) who found that African-American communities generally hold less negative cultural values about being heavy, a clear limitation of the study by Wang et al (2004) was the sample size, which may not have provided sufficient power to detect ethnic differences.…”
Section: The Impact Of Race Culture and Ethnicitymentioning
confidence: 99%
“…Similarly, Wang, Brownell and Wadden (2004) found that African Americans held less strong implicit weight bias compared to Caucasians. While Wang et al (2004) had originally hypothesised that African-American participants were less likely to show in-group devaluation than Caucasians, based on research by Ofosu, Lafreniere and Senn (1998) who found that African-American communities generally hold less negative cultural values about being heavy, a clear limitation of the study by Wang et al (2004) was the sample size, which may not have provided sufficient power to detect ethnic differences.…”
Section: The Impact Of Race Culture and Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Otro aspecto relevante mencionado en diversas investigaciones es que, a diferencia de lo que ocurre con otros grupos estigmatizados, las personas obesas se estigmatizan a sí mismas tanto como lo hacen otras personas no obesas 6,13,15,16 , teniendo consecuencias negativas en las víctimas y también en las personas con quienes interactúa. Lo anterior incluye a los equipos de salud que intervienen en esta patología, ya que prácticas discriminatorias derivadas del estigma de obesidad podrían dar lugar a la evitación de los entornos de salud y a la baja adherencia terapéutica de la intervención con especialistas 3,17,18 .…”
Section: Contextualización General Del Estigma De Obesidadunclassified